Environmental Learning - Rickinson, Mark. author. aut Link
XI, 147 p.
Keywords: Environmental education and education for sustainable development have become features of many countries’ formal education systems. To date, however, there have been few attempts to explore what such learning looks and feels like from the perspective of the learners. Based on in-depth empirical studies in school and university classrooms, this book presents rich insights into the complexities and dynamics of students’ environmental learning. The authors show how careful analysis of students’ environmental learning experiences can provide powerful pointers for future practice, policy and research. Environmental Learning will be a key resource for educators, teacher educators, decision-makers and researchers involved in education and sustainable development.